2019
DOI: 10.3390/ijerph16193539
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Associations between Educational Attainment and Occupational Stress across Racial and Ethnic Groups

Abstract: Background: Although other mechanisms are also involved, at least one reason high educational attainment (EA) is associated with better health is lower employment stress in individuals with high EA. Minorities’ Diminished Returns, however, refer to the smaller protective health effects of EA for racial- and ethnic-minority individuals, particularly African Americans (AAs) and Hispanics, as compared to Whites. We are, however, not aware of many studies that have explored differential associations between EA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 49 publications
4
73
0
Order By: Relevance
“…The observation that as income increases, the psychological well-being of middle-aged and older adults improves, but less for immigrants than non-immigrants, is an extension of previous literature on MDRs 21,22 of income, [23][24][25][26][27] educational attainment, 36 occupation, 29,30 and marital status 46 on a wide range of mental health outcomes, including psychological distress, 54 depression, 24,55 suicide, 31 and anxiety. 46 These MDRs go beyond physical health outcomes and extend to behavioral outcomes such as vaping, 33 smoking, 35,42,44,56,57 drinking, 34,58 diet, 59 and exercise.…”
Section: Discussionmentioning
confidence: 71%
“…The observation that as income increases, the psychological well-being of middle-aged and older adults improves, but less for immigrants than non-immigrants, is an extension of previous literature on MDRs 21,22 of income, [23][24][25][26][27] educational attainment, 36 occupation, 29,30 and marital status 46 on a wide range of mental health outcomes, including psychological distress, 54 depression, 24,55 suicide, 31 and anxiety. 46 These MDRs go beyond physical health outcomes and extend to behavioral outcomes such as vaping, 33 smoking, 35,42,44,56,57 drinking, 34,58 diet, 59 and exercise.…”
Section: Discussionmentioning
confidence: 71%
“…Previous work has documented MDRs in terms of effects of educational attainment on job quality. For example, highly educated Black people work in high stress jobs, while highly educated White people work in low stress jobs (47). Another study showed that highly educated non-Hispanic Black people work in jobs that are high in second-hand tobacco exposure, while highly educated non-Hispanic White people work in jobs with low second-hand tobacco exposure (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…The rst proposed mechanisms is the labor market discrimination (44). Under labor market discrimination, highly educated Blacks may have a lower chance to secure high quality, low stress, and high paying jobs (45)(46)(47). Thus highly educated non-Hispanic Blacks make lower income and are more likely to live under poverty despite high educational level, compared to non-Hispanic Whites with the same education (44,48,49).…”
Section: Due To Multiple Societal Mechanisms Ses Indicators May Genementioning
confidence: 99%
“…[7][8][9][10][11] The protective effect of education against occupational stress has also been found to be lower among NHBs relative to NHWs. 12 Consequently, work-related stress generally and perceived workplace discrimination in particular, may play a role in the CVD morbidity and mortality disparities observed among NHBs. Conversely, selfemployed NHBs may face more financial uncertainty, relative to NHB wage workers, potentially increasing stress levels and worsening health outcomes.…”
Section: Introductionmentioning
confidence: 99%